Where's the Moon? : A Memoir of the Space Coast and the Florida Dream - McCutchan, Ann (Book collections on Project MUSE., 2016)
When you lose your parents just as you have left home for graduate school-glad to finally be away from a life and place you found stifling-how do you make your way in a world with no home to go back to? For Ann McCutchan, whose parents died in a car accident when she was twenty-three, the answer was to keep moving, away from the dream her mom and dad had so hopefully embraced in her childhood, and away from the locus of that dream, the state of Florida in the 1960s. In this coming-of-age memoir, McCutchan returns to Florida to reconcile with the life she had there. Reconnecting with old friend.